Evidence-Based Dentistry: The Next Frontier in Translational and Trans-National Dental Practice - Reem Ajaj; André Barkhordarian; Linda Phi; Amy Giroux; Francesco Chiappelli (Wolters Kluwer Medknow Publications, 2011)
Evidence-Based Dentistry (EBD) is a systematic approach for ob-taining the best available clini-cally relevant scientific evidence with the ultimate goal and intent of increasing effectiveness and efficacy in clinical decision-making. EBD pursues optimizing both the patient's benefit through the best utilization of dentist's experience and clinical expertise, and on making full use of the most reliable and va-lid research outcomes. EBD is initiated by the patient-dentist interaction, which is translated into a patient-centered P.I.C.O. question. The resulting literature bibliome is assessed and quantified for the level and quality of the evidence by means of fully validated and reli-able instruments based on common standard criteria of research methodology, design and statistical analysis. The outcomes are evaluated by acceptable sampling analysis, Such that studies, whose flaws have been identified to result potentially into misleading infor-mation to the patients and/or practitioner may be judiciously removed from further consideration". The research synthesis process tests for overarching statistical sig-nificance among non-heterogeneous outcomes, and yields a consensus of the best available evidence. The systematic nature of the re-search review and synthesis that characterizes EBD is reported in the literature as "systematic reviews", "complex systematic reviews", or "clinically relevant complex systematic reviews". Thus the reported best available evidence ensures patient-centered clinical decision for interventions of the highest possible effectiveness and effi-cacy. EBD contrasts with traditional dentistry based on the evidence for its systematic stringency, coupled with its fundamental validity as a patient-centered optimization of clinical modes of interventions.